Effect of scaling and root planing as monotherapy on glycemic control in patients of Type 2 diabetes with chronic periodontitis: A systematic review and meta-analysis - Akanksha Jain; Jyoti Gupta; Dipika Bansal; Shaveta Sood; Shipra Gupta; Ashish Jain (Wolters Kluwer Medknow Publications, 2019)
Background: There is enough evidence, which suggests that nonsurgical periodontal therapy (NSPT) improved the glycemic control in patients of Type 2 diabetes mellitus (T2DM) with chronic periodontitis (CP). This meta-analysis is aimed to explore the effect of NSPT, exclusively scaling and root planing (SRP) as monotherapy on glycemic control and periodontal parameters in patients of T2DM with CP. Materials and Methods: Two databases, MEDLINE and EMBASE, were searched from June 2006 to June 2016. Initially, 464 potentially relevant studies were evaluated. Randomized controlled trials with duration of ≥3 months, based on the treatment group managed with SRP without any supportive use of local drug delivery or systemic antibiotics, while the control group received no periodontal therapy, were selected. This resulted in six appropriate articles with a total of 812 patients of T2DM with CP. Alteration in glycated hemoglobin (HbA1c) was the primary outcome measure, whereas the changes in clinical attachment level (CAL) and probing pocket depth (PPD) were the secondary outcome measures. Results: SRP treatment resulted in a decrease in HbA1c by 0.26% (P = 0.17) at 3-4 months compared to the control group. Further, on subgroup analysis, SRP therapy revealed a decrease in PPD and CAL at 3-4 months, though statistically insignificant. Conclusion: SRP treatment leads to modest improvement in glycemic status and periodontal parameters in T2DM patients with CP at 3-4 months.